2021
DOI: 10.2166/ws.2021.163
|View full text |Cite
|
Sign up to set email alerts
|

Drought indices: aggregation is necessary or is it only the researcher's choice?

Abstract: Drought is a natural phenomenon caused by extreme and persistent precipitation shortage. This shortfall causes impacts on hydrology, agriculture, and the economy of a country. Secondly, drought/dryness has certain unique characteristics (severity, duration) among the natural hazards which makes it difficult to classify the persistent and subjective network of impacts. Drought classification is important to manage drought, allowing both quantitative evaluation and potential risk assessment planning. The simpler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…Drought indices are important instruments for defining and monitoring drought because they simplify complex meteorological functions and can quantify climatic abnormalities in terms of severity, length, and frequency [38,39]. Moreover, over the last few decades, many studies have been conducted to monitor the drought in Ethiopia, and most of these studies are SPI-based drought [40,41] analyses based on location-specific observed or stationed rainfall data.…”
Section: Introductionmentioning
confidence: 99%
“…Drought indices are important instruments for defining and monitoring drought because they simplify complex meteorological functions and can quantify climatic abnormalities in terms of severity, length, and frequency [38,39]. Moreover, over the last few decades, many studies have been conducted to monitor the drought in Ethiopia, and most of these studies are SPI-based drought [40,41] analyses based on location-specific observed or stationed rainfall data.…”
Section: Introductionmentioning
confidence: 99%
“…Evapotranspiration is affected by climatological and meteorological factors in a region, such as solar radiation, temperature, humidity, and teleconnection patterns. It is also one of the most important variables in studying dryness stress of the plants and monitoring agricultural drought conditions, which are used in the calculations of drought indices like the Standardized Precipitation-Evapotranspiration Index and Palmer Drought Severity Index [1,2]. erefore, its accurate measurement at the farm level is crucial and necessary for farmers and managers, as well as planners of agricultural water resources.…”
Section: Introductionmentioning
confidence: 99%
“…A shorter time scale (1 month) was selected to calculate the drought duration because at this scale SPI, SSI, and SSMI can capture more drought events than larger timescale. Previous studies mentioned that a larger time scale (e.g., 9–12 months) is sensitive for long drought events (Faiz et al ., 2021; Wu et al ., 2021a). During the analysis, it was found that the duration of M droughts events ranged between 1 and 3 months before the change point in YRB, while after the change point, it showed 2 and 4 months.…”
Section: Resultsmentioning
confidence: 99%